Mainstreaming 21st century African feminisms in interpreting gender-based violence in the African Union human rights system - Budoo-Scholtz, Ashwanee (University of Pretoria, 2021)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2021.